The Use of E-commerce on the Behaviour and Lifestyle of Buying Products Online among Students of the University of Sumatera Utara - Tampubolon, Argindo Pratama; Zulkarnain, Iskandar; Mazdalifah, Mazdalifah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of using E-Commerce on online buying behavior among North Sumatra University students, the effect of using E-Commerce on the lifestyle of North Sumatra University students, and the effect of using E-Commerce on product buying behavior and lifestyle. University of North Sumatra students. This study uses quantitative methods using correlational methods. The results showed that there was an effect of using E-Commerce as a medium for buying products online with the buying behavior of University of North Sumatra students with a correlation value of 0.293 which shows a low but definite level of influence. There is an influence of the use of E-Commerce in the lives of students at the University of North Sumatra with a correlation value of 0.296 indicating a low but definite level of influence. There is an effect of using E-Commerce as a medium for buying products online with the buying behavior and lifestyle of North Sumatra University students of 0.284 which shows a low but definite level of influence. In addition, the results of the positive correlation value show a unidirectional effect.